Muhasabah as A Moderator Variable To Strengthen The Relationship Between Neuro Linguistic Programming and Subjective Well-Being - Muhammad Nurhalim (Pelopor Publikasi Akademika, 2023)
The purpose of this study is to conduct an analytical study of the concept of muhasabah as a moderator variable to strengthen the relationship between Neuro Linguistic Programming (NLP) and Subjective well-being. The research method used is a qualitative study with a descriptive approach through a review of a number of literature on mu??sabah, NLP and Subjective well-being then looking for common ground for improving Subjective well-being. The analysis was carried out using Schleiermacher's hermeuntic theory. The results showed that (1) that the muhasabah step can be a moderator variable to strengthen the relationship between NLP and Subjective well-being; (2) the integration of Muhasabah into NLP practice or vice versa is important to be carried out in order to strengthen the discourse of Islamic psychology as the current trend develops.